How government-public collaboration affects individual mitigation responses to flooding: A case study in Yellow River Delta area, China - Xie, Lei; Wang, Yijie; Li, Shuang (Forestry Faculty, Universitas Hasanuddin, 2023)
In the top-down Chinese political system, flood management has traditionally been led by the government, with the general public playing a supporting role. Within this context, individual-level disaster prevention behaviors are strongly interacted with the government-public collaboration during the government-led flood management processes. This study aims to provide a comprehensive understanding of how government-public collaboration affects individuals’ flood mitigation responses in China. An online survey data with 550 respondents from the Yellow River Delta area was examined with regard to the individuals’ willingness to take positive mitigation actions, and ordinal logistic regression models were constructed to explore the influence of the government-public collaboration factors, which are digested into three aspects: public involvement, public awareness and political trust, that motivate individuals to take flood mitigation measures. The results demonstrate that public involvement and political trust are positively correlated with the likelihood of individuals’ adopting positive mitigation actions, while public awareness and self-reported preparedness were also positively correlated, although to a less significant degree. This study contributes to the current literature by increasing the understanding of how government-public collaboration determines individual mitigation actions in the Chinese collectivist cultural environment. The results of this study reveal that involving the public effectively and earnestly through various forms of community engagement are likely to promote individual-level disaster prevention behaviors, from this point of view, can help policymakers to guide local residents towards taking responsible flood risk management and preventative actions.